Atypical presentation of acute retinal necrosis mimicking Vogt-Koyanagi-Harada disease leading to misdiagnosis: a case report - Zhu, Wei; Yu, Cuiyun; Guo, Qianqian; Kang, Qingran; Cao, Xusheng (Frontiers in Medicine, 2024)
Acute retinal necrosis (ARN) is a serious, sight-threatening condition characterized by rapidly progressive necrotizing retinitis, most commonly caused by varicella-zoster virus and herpes simplex virus. We report an atypical case of ARN in a 57-year-old immunocompetent male, initially misdiagnosed as Vogt-Koyanagi-Harada (VKH) disease. This case highlights the challenges in the early differential diagnosis of infectious and non-infectious uveitis. Misdiagnosis can lead to a delay in initiating antiviral therapy, potentially accelerating disease progression and worsening visual outcomes.